2008
DOI: 10.3171/foc/2008/24/3-4/e13
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors, stem cells, and stroke

Abstract: ✓ Postischemic neurogenesis has been identified as a compensatory mechanism to repair the damaged brain after stroke. Several factors are released by the ischemic tissue that are responsible for proliferation, differentiation, and migration of neural stem cells. An understanding of their roles may allow future therapies based on treatment with such factors. Although damaged cells release a variety of factors, some of them are stimulatory whereas some are inhibitory for neurogenesis. It is interesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…NSCs not only have the multiple potentials of differentiation, but also can migrate and differentiate in response to signals stimulated by tissue damage [35]. In this study, we found that transplanted NSC, NSC-GFP or NSC-bFGF differentiated into neurons and astrocytes.…”
Section: Discussionmentioning
confidence: 55%
“…NSCs not only have the multiple potentials of differentiation, but also can migrate and differentiate in response to signals stimulated by tissue damage [35]. In this study, we found that transplanted NSC, NSC-GFP or NSC-bFGF differentiated into neurons and astrocytes.…”
Section: Discussionmentioning
confidence: 55%
“…FGF-2 is a potent neurogenic factor promoting early neurogenesis, supporting proliferation of neural stem cells and progenitors and enhancing the survival of mature neurons. [69][70][71][72] Moreover, a reduction in FGF-2 expression and an increase in FGF receptor expression in the frontal cortex and hippocampus were observed in post-mortem human brain samples of patients suffering from major depression. 73,74 Similarly, animal models further support the role of the FGF system in depression and its potential involvement in antidepressant treatment.…”
Section: Discussionmentioning
confidence: 92%
“…In the adult brain, MMP-3 and -9 have been shown to be expressed by NPCs, and inhibition of MMPs in in vitro siRNA experiments, as well as MMP inhibitors in a mouse model, have revealed a reduction in NPC migration following MCAO ischemia [120,121] . The working hypothesis is that MMPs released by the NPCs digest the ECM to clear the path for neuroblast migration [122] . Considering that MMPs are also expressed by endothelial cells and astrocytes [123,124] and in light of the increased gliosis that occurs following stroke, these cells may also be contributing to the enhanced migration of NPCs following stroke.…”
Section: Migrationmentioning
confidence: 99%